A Coach's Communication Strategy and its Relationship to a Collegiate Player's Motivation to Perform as an Athlete. - Neil, Dana; Pendergast, Andrea; Schmidt, Amy; Soricelli, Maria; Taylor, Melissa (My University, 2009)
Our research project was designed to measure the variables of "coaches' communication strategies" and "collegiate players' motivation to perform as an athlete." We decided to research this topic because at one time or another we all have been on a sports team and experience different types of coaching strategies. We were interested to know how current athletes viewed their coaches' communication strategies and what effect it had on their motivation to perform.
A Coach's Communication Strategy Related to a Collegiate Player's Motivation to Perform as an Athlete
Color poster with text, table, and graph describing research conducted by Dana Neil, Andrea Pendergast, Amy Schmidt, Maria Soricelli, and Melissa Taylor, advised by Jennifer Becker.
Keywords: Coaching--Psychological aspects; Communication in sports; Motivation (Psychology); Sports--Psychological aspects; Posters